Monetisation and commercialisation in the Baltic Sea, 1050-1450
1 online resource.
Keywords: "Monetisation and Commercialisation in the Baltic Sea, 1050-1450 explores the varied uses of silver and gold in the Baltic Sea zone during the medieval period. Ten original contributions examine coins and currencies, trade, economy, and power, taking care to avoid an out-of-date approach to economic history which assumes a progression from 'primitive' forms to 'developed' structures. Combining a variety of methodological approaches, and drawing on written sources, archaeological and numismatic evidence, and anthropological perspectives, the book considers the various ways in which silver and gold were used as monetary currency, fiscal instruments of power, and gifts in the High and Late Medieval societies of the Baltic Sea. This book will appeal to scholars and students of medieval European history, as well as those interested in economic history, and the history of trade and commerce"--